Competitiveness as a tool for business strengthening and for the traders of the urban area of Duran canton, Guayas province, 2023. - Bravo Carrasco, Alex Rodolfo; Rosillo Toro, Willian; Vivanco Hidalgo, Isauro (Conexiones UG, 2023)
The issue faced by traders in the Durán Canton Market, Guayas Province in 2023 is closely related to business development. The lack of organizational control has revealed significant limitations in the economic progress of the region. The objective of this study is to identify and analyze competitiveness as a tool for strengthening businesses among traders in the urban area of Durán Canton, Guayas Province, in 2023.This study adopts a qualitative approach and employs a non-experimental, cross-sectional, and descriptive research methodology. The investigation involved searches in academic sources such as Google Scholar, E Library, Redalyc,RefSeek, among others. The results revealed that traders in the urban area of Durán Canton play a fundamental role in the country’s economy but face significant deficiencies in theirmanagement, which affects their competitive capacity. To address this issue, it is proposed to provide training and guides to the region’s microentrepreneurs. These guides will cover topics related to administrative management, accounting, and organizational skills with the aim of improving efficiency and fostering a more robust business environment.
Keywords: Merchants; competitiveness; business strengthening